2011
DOI: 10.4067/s0718-95162011000400008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of organic and conventional apple orchard management on soil chemical properties and plant mineral content under Mediterranean climate conditions

Abstract: The effects of conventional and organic management systems on soil chemical properties and leaf nutrients under Mediterranean conditions were studied over a 2-year period on adjacent commercial apple orchards in Southern Greece. The soil in both orchards was characterised as a clay loam-clay and was uniform in morphological and physical properties. The results indicated no significant differences in soil chemical properties between the different management systems, including soil organic matter (SOM), pH, cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 26 publications
6
29
0
1
Order By: Relevance
“…Regarding leaf mineral concentrations our results are comparable to those reported by Gasparatos et al (2011), who compared effects of organic and conventional apple orchard management on plant mineral content which was not significantly affected by treatments.…”
Section: Discussionsupporting
confidence: 80%
“…Regarding leaf mineral concentrations our results are comparable to those reported by Gasparatos et al (2011), who compared effects of organic and conventional apple orchard management on plant mineral content which was not significantly affected by treatments.…”
Section: Discussionsupporting
confidence: 80%
“…Organic farming is increasing in popularity around the world and plays an important role in agriculture [7]; it is seen as an alternative to conventional farming, as well as a solution for sustainable development [8]. Previous studies have not revealed any differences in soil organic matter between conventional and organically grown apples [6].…”
Section: Introductionmentioning
confidence: 99%
“…Apple growing requires high capital investment [5] and the choice of production system (organic or conventional) has a direct impact on apple orchard productivity [6]. Organic farming is increasing in popularity around the world and plays an important role in agriculture [7]; it is seen as an alternative to conventional farming, as well as a solution for sustainable development [8].…”
Section: Introductionmentioning
confidence: 99%
“…According to Vaněk, Šilha and Němeček [26], it can also be as result of the activities of leguminous crops in which case bambara groundnut is one. The CEC of soil samples in this study (between 15.19 and 21.64 meq/100g) fall within the range of CEC of organically and conventionally managed apple orchard ranging from 19.23 to 20.28 cmol/kg [27], even though no fertilizer or organic manure was applied to bambara groundnut in this study.…”
Section: Discussionmentioning
confidence: 51%